1994
DOI: 10.1038/bjc.1994.58
|View full text |Cite
|
Sign up to set email alerts
|

Increase in mast cells and hyaluronic acid correlates to radiation-induced damage and loss of serous acinar cells in salivary glands: the parotid and submandibular glands differ in radiation sensitivity

Abstract: Summary The detailed mechanisms which can explain the inherent radiosensitivity of salivary glands remain to be elucidated. Although DNA is the most plausible critical target for the lethal effects of irradiation, interactions with other constituents, such as cell membrane and neuropeptides, have been suggested to cause important physiological changes. Moreover, mast cells seem to be closely linked to radiation-induced pneumonitis. Therefore, in the present study the effects of fractionated irradiation on sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 23 publications
5
35
0
3
Order By: Relevance
“…The same authors also reported recently that a single dose of 2.5 Gy to the rat significantly reduced parotid salivary flow rate 12 months after irradiation (32). A more pronounced radiosensitivity of the parotid than the submandibular glands has also been suggested from morphological evaluations (33). The concentration of potassium in saliva, but not the total output, increased with time and irradiation doses up to 6 Gy x 5.…”
Section: Discussionmentioning
confidence: 58%
“…The same authors also reported recently that a single dose of 2.5 Gy to the rat significantly reduced parotid salivary flow rate 12 months after irradiation (32). A more pronounced radiosensitivity of the parotid than the submandibular glands has also been suggested from morphological evaluations (33). The concentration of potassium in saliva, but not the total output, increased with time and irradiation doses up to 6 Gy x 5.…”
Section: Discussionmentioning
confidence: 58%
“…Histological studies have reported that normal parotid glands are filled with homogenous serous acinar cells that contain densely packed translucent secretory granules. 39,40 Those densely packed cells and granules provide uniform and highly reflective interfaces for the ultrasound beam, 41 producing for the homogeneous and hyperechoic appearance of the normal parotid glands. After irradiation, many acini are lost with the remaining acini appearing larger than normal and more disorganized.…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed in an in vitro study showing that muscarinic receptor-induced calcium mobilization and protein kinase C activation were affected ). The late effects of radiation on the parotid and submandibular glands have been studied less extensively, and have been reported as a dose-dependent further decline in function (Nagler et al, 1998;) and loss of acinar cells (Henricksson et al, 1994;O'Connell et al, 1999). Unfortunately, in the latter studies the whole or half of the head including the glands was irradiated.…”
Section: Salivary Glandsmentioning
confidence: 99%
“…Within three days after irradiation with a single dose of 15 Gy of x-rays, a decrease in salivary flow of nearly 50% can be observed (Vissink et al, 1990;Peter et al, 1995;Coppes et al, 1997aCoppes et al, ,b, 2001Zeilstra et al, 2000). Lack of obvious quantitative morphological alterations (Franzén et al, 1991;Henricksson et al, 1994;Zeilstra et al, 2000;, a rather quick recovery of the morphological changes if they occur (Vissink et al, 1991), and a lack of increase in apoptotic cells early after radiotherapy (Paardekooper et al, 1998) point to the presence of altered cell membranes (Sodicoff et al, 1974;El Mofty and Kahn, 1981;Vissink et al, 1992) and/or a disturbed intracellular signaling (Vissink et al, 1991;Coppes et al, 1997b) as the cause of the early effect of radiation on the parotid gland. This was confirmed in an in vitro study showing that muscarinic receptor-induced calcium mobilization and protein kinase C activation were affected ).…”
Section: Salivary Glandsmentioning
confidence: 99%